City branding in Indonesia: the urgency of public communication, involvement, and inter-sectoral collaboration - Lestari, Forina; Melasutra MD Dali,; Norbani Che-Ha, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Contemporary cities are facing various challenges, both internally and externally. Indonesian cities are not exempted from this phenomenon. In light of this, city branding has become a widespread practice undertaken by most city managers to attract visitors, tourists, and investors. This study is trying to capture the city branding implementation in Indonesia and suggests several improvement strategies in tourism development. This study is using content analysis to explore existing literature on city branding implementation in several cities in Indonesia over the last ten years. A summary of more than thirty studies is provided along with the content analysis. The finding of these studies gives a significant contribution to the field of city branding that focuses on practical operational in social and governance dimensions in the local context. It shows that the limitation of understanding on city branding concept from the local authorities in many cities has resulted in less efficient and effective branding. City branding in most cities in Indonesia was trapped merely in making slogan and logos with less consideration in public aspirations and local identities. In addition, the common problem of lack of intersectoral coordination has resulted in a situation where branding has been undertaken solely by the tourist management sectors without proper support from other sectors. This study emphasizes the urgency of public involvement and inter-sectoral collaboration in ensuring city branding successfulness.